The participation of clinical pharmacists in the treatment of patients with central nervous system infection can improve the effectiveness and appropriateness of anti-infective treatments: a retrospective cohort study - Cheng, Jie; Dang, ChuanDong; Li, Xiao; Wang, JianJun; Huang, Xin; Li, Yan; Cui, XueYan (Frontiers in Pharmacology, 2023)
Background: Central nervous system infection (CNSI) treatment in hospital neurosurgery emphasizes the importance of optimizing antimicrobial therapy. Timely and appropriate empiric antibiotic treatment is critical for managing patients with bacterial meningitis. Objectives: To evaluate the activities of clinical pharmacists in the anti-infective treatment of patients with CNSI in neurosurgery. Method: A single-center retrospective cohort study was carried out from April 2021 to March 2023 at a tertiary teaching hospital in China. The study sample included a group that received pharmacy services and a group that did not. In the pharmacy services group, the anti-infective treatment plan was led and developed by pharmacists. Pharmaceutical care, including medication therapy and all CNSI treatment regimens, was administered in daily unit rounds by pharmacists. Baseline demographics, treatment outcomes, and rational use of antibiotics were compared between the two groups, and the impact of a antimicrobial stewardship (AMS) program was evaluated. Results: Of the 306 patients assessed according to the inclusion and exclusion criteria, 151 patients were included, and 155 patients were excluded due to abnormal data and missing information on antibiotic costs or antimicrobial use. Eventually, 73 were included in the pharmacy services group experimental group and 78 in the group without pharmacist participation. The antibiotic use density (AUD) of the pharmacy services group decreased from 167.68 to 127.63 compared to the group without pharmacist participation. After the pharmacist services, the AUD for linezolid decreased from 9.15% to 5.23% and that for miscellaneous agents decreased from 17.91% to 6.72%. The pharmacy services group had better improvement (P <0.05) and a significantly higher score for the rational use of antibiotics (P <0.05) than the group without pharmacist participation. Conclusion: The clinical pharmacist services evaluation results demonstrated an essential role of clinical pharmacist-led AMS programs in the effective and appropriate use of anti-infective treatments in neurosurgery with patients with CNSI.